PENGARUH SAHAM SYARIAH, OBLIGASI SYARIAH, DAN REKSADANA SYARIAH TERHADAP REAKSI PASAR MODAL DI INDONESIA (Studi Kasus Pada Indeks Efek Syariah Di Indonesia Tahun 2015-2017) - Fajri Nasrullah; Jeni Susyanti; Muhammad Agus Salim (E-JRM : Elektronik Jurnal Riset Manajemen, 2019)
Abstract This study aims to empirically examine the influence of Islamic stocks, Islamic bonds, and Islamic mutual funds on the reaction of the capital market in Indonesia, 36 samples used in this study. Quantitative research uses data collection techniques in this study using secondary data and the data used are in the form of financial statements, joint stock price indices, Islamic stock indices, Islamic bond indexes, and Islamic mutual fund indexes. Data analysis methods used include morality test, classic assumption test, multiple linear regression analysis, coefficient of determination, and hypothesis testing.The results of the analysis show that Islamic stocks and Islamic mutual funds partially have a significant positive effect on the reaction of the capital market in Indonesia and Sharia bonds partially have a significant negative effect on the reaction of the capital market in Indonesia. Simultaneous testing of Islamic stocks, Islamic bonds, Islamic mutual funds has a significant positive influence on the reaction of the capital market in Indonesia.Keywords: Sharia Stocks, Sharia Bonds, Sharia Mutual Funds, and Capital Markets.